The complete mitochondrial genome of Aconitum kusnezoffii Rchb. (Ranales, Ranunculaceae). Issue 3 (4th March 2021) - Li, Sheng-Nan; Yang, Yan-Yun; Xu, Liang; Xing, Yan-Ping; Zhao, Rong; Ao, Wu-Liji; Zhang, Ting-Ting; Zhang, Da-Chuan; Song, Yue-Yue; Bao, Gui-Hua; Kang, Ting-Guo
Abstract: Aconitum kusnezoffii Rchb. is a medicinal plant in the Ranunculaceae family. In this study, we report the first complete mitochondrial genome of A. kusnezoffii . The total length of the mitochondrial genome of A. kusnezoffii is 440, 720 bp and the GC content of 46.85%. The mitochondrial genome contained 37 protein-coding genes, 29 tRNAs, and three rRNAs. These data will provide the basis for the systematic evolutionary analysis of Ranunculaceae.